Minimum 5-year follow-up outcomes for single-stage transpedicular debridement, posterior instrumentation and fusion in the management of thoracic and thoracolumbar spinal tuberculosis in adults. (1st November 2016) - Zhang, Penghui; Peng, Wei; Wang, Xiyang; Luo, Chengke; Xu, Zhengquan; Zeng, Hao; Liu, Zheng; Zhang, Yupeng; Ge, Lei
Abstract: Aim: The aim of this retrospective clinical study is to evaluate the long-term outcomes for single-stage transpedicular debridement, posterior instrumentation and fusion in the management of thoracic and thoracolumbar spinal tuberculosis in adults. Methods: Fifty-nine adult patients with thoracic and thoracolumbar spinal tuberculosis underwent single-stage transpedicular debridement, posterior instrumentation and fusion. These patients were followed for a minimum of 5 years. Patients were assigned to one of two groups according to the infected anatomic segment. In the thoracic spinal tuberculosis group, there were 28 cases (17 males, 11 females) with a mean age of 38.9 years; in the thoracolumbar spinal tuberculosis group, there were 31 cases (19 males, 12 females) with a mean age of 40.3 years. All cases were evaluated clinically using the visual analog scale (VAS), Kirkaldy–Willis criteria and the American Spinal Injury Association (ASIA) impairment scale. Radiographs were performed for measuring the angle of kyphosis and scoliosis. Complications related to surgery were recorded. Results: All patients successfully resolved their infections, experienced one or more ASIA grades of improvement, and improved in their VAS pain scores at final follow-up. In both groups, patient-reported outcomes reached over 90% excellent or good results using Kirkaldy–Willis criteria. The loss of kyphotic angle correction was 2.6° in the thoracic spinal tuberculosis group and 3.2° in the thoracolumbar spinal tuberculosis group. No scoliosis was observed in either group. Fifty-eight (98.3%) cases achieved solid bony fusion. In the thoracolumbar spinal tuberculosis group, one patient experienced screw loosening, and another patient with nonunion and rod breakage underwent revision surgery. Conclusions: The technique of single-stage transpedicular debridement, posterior instrumentation and fusion is an effective method for the treatment of thoracic and thoracolumbar spinal tuberculosis in adults. Long-term postoperative clinical and radiological outcomes were satisfactory.